2013
DOI: 10.1097/dad.0b013e3182819da6
|View full text |Cite
|
Sign up to set email alerts
|

Immunohistochemical Expression of GLUT-1 and Ki-67 in Chronic Plaque Psoriasis

Abstract: Many inflammatory mediators and other biological markers are upregulated in psoriatic lesions; some of these alterations also persist in nonlesional skin. Glucose is the major source of energy for cells, and glucose transporter 1 is the most common glucose transporter in humans (GLUT-1). The present study aimed at evaluating the pattern of expression of GLUT-1 and Ki-67 in psoriatic skin (involved and uninvolved) and correlating their expression with the clinicopathological parameters in the studied patients. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
19
1
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(25 citation statements)
references
References 18 publications
4
19
1
1
Order By: Relevance
“…The present study detected statistically significant positive correlation between GLUT‐1 expression in psoriasis lesions and the mean of epidermal thickness, which is an indicator of epidermal hyperproliferation. This finding was in agreement with the results of Abdou et al . and Tochio et al .…”
Section: Discussionsupporting
confidence: 94%
See 3 more Smart Citations
“…The present study detected statistically significant positive correlation between GLUT‐1 expression in psoriasis lesions and the mean of epidermal thickness, which is an indicator of epidermal hyperproliferation. This finding was in agreement with the results of Abdou et al . and Tochio et al .…”
Section: Discussionsupporting
confidence: 94%
“…These results add further support to previous studies done by Tao et al . and Abdou et al . who suggested that the upregulation of GLUT‐1 in psoriasis lesions could participate in the pathogenesis of psoriasis through the facilitation of glucose transport, which is required to satisfy the needs of rapid hyperproliferative keratinocytes.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…16 This overexpression of GLUT-1 in cutaneous SCC and other malignancies may govern mechanisms that favor tumor growth at the expense of host tissues. 17 It is unknown whether elevated GLUT-1 expression accurately reflects the hypoxic state of the tumor or whether elevated GLUT-1 levels are an indication of the altered metabolic state of tumor cells.…”
Section: Discussionmentioning
confidence: 99%